2019
DOI: 10.20870/oeno-one.2019.53.2.2427
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in Vitis vinifera L. cv. Pinot noir fruit and wine quality in relation to climate

Abstract: Aims: A better understanding of the relationship between weather conditions and wine quality would provide tools for assessing the impact of climate change and the potential for adaptation. Most studies rely on assessing wine quality by the price per bottle or by an overall ranking and then establishing general relations to weather conditions. However, such an approach may imply the addition of bias by variable winemaking techniques overcoming vintage effects. The aim of our study was therefore to implement a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…As can be seen, the musts from harvest 03 (V03) were located in the most distant area from the defects (lactic, musty, herbaceous and chemical character), with no influence from the variety or the raisining method. This would confirm the important influence of the vintage on the quality of raisin musts, as some authors had already pointed out in previous studies [37,38]. 4.2 ± 0.9 2.9 ± 0.8 0.7 ± 0.4 3.0 ± 1.1 3.4 ± 1.0 0.9 ± 0.5 1.9 ± 0.6 0.7 ± 0.4 0.9 ± 0.7 0.3 ± 0.6 0.2 ± 0.3 1.2 ± 0.5 3.7 ± 0.…”
Section: Effect Of the Raisining Methods On The Aroma Of Raisin Mustssupporting
confidence: 89%
“…As can be seen, the musts from harvest 03 (V03) were located in the most distant area from the defects (lactic, musty, herbaceous and chemical character), with no influence from the variety or the raisining method. This would confirm the important influence of the vintage on the quality of raisin musts, as some authors had already pointed out in previous studies [37,38]. 4.2 ± 0.9 2.9 ± 0.8 0.7 ± 0.4 3.0 ± 1.1 3.4 ± 1.0 0.9 ± 0.5 1.9 ± 0.6 0.7 ± 0.4 0.9 ± 0.7 0.3 ± 0.6 0.2 ± 0.3 1.2 ± 0.5 3.7 ± 0.…”
Section: Effect Of the Raisining Methods On The Aroma Of Raisin Mustssupporting
confidence: 89%
“…However, the biochemical and molecular mechanisms involved downstream of the MA metabolic pathways are still raveled, and an unclear slower drop in MA content has been observed in cooler regions (Sweetman et al, 2014). MA degradation appears to be slower in cool climates, where it represents up to the 50 % of total acidity in berry juice (Jackson, 2008), and faster in warmer regions, as reported for Pinot noir by Blank et al (2019). This negative correlation between MA content and high temperatures are ascribed to the differences observed in the optimum activity temperatures of enzymes involved in the biosynthesis and catabolism of MA (Conde et al, 2007); therefore, climatic conditions and environmental stressors can physically and biochemically affect grapevine berries during the ripening period, as well as influence the final sugar/organic acid ratio (Volschenk et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…MA is also sensitive to warm temperatures both before and after véraison, when process linked to the biosynthetic pathway and the respiration process respectively take place (Kliewer et al, 1967;Ruffner et al, 1984). Many studies reported the negative correlation between high temperatures and MA content after véraison (Sweetman et al, 2014;Rienth et al, 2016;Blank et al, 2019). However, the biochemical and molecular mechanisms involved downstream of the MA metabolic pathways are still raveled, and an unclear slower drop in MA content has been observed in cooler regions (Sweetman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Climate characterization and monitoring of grapevine phenology and berry biochemistry are efficient tools to define environmental vulnerability of wine regions and create basis for addressing strategies for future planning of viticulture practices [19]. Understanding of the interaction between weather conditions and berry/wine compounds will help with developing improved winemaking techniques as a part of adapting to future impacts of climate change [20]. Temperature is an essential factor influencing duration of phenophases.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important climate change related effects are advanced harvest time and temperatures, increased grape sugar concentrations that lead to high wine alcohol levels, lower acidities and modification of varietal aroma compounds [18]. In cooler wine regions sugar accumulation is positively influenced by warmer conditions during veraison while malic acid content decreases [20].…”
Section: Introductionmentioning
confidence: 99%